Application of value engineering technique and its reflection on cost leadership strategy (Journal of Madenat Alelem, 2025)
The research aims to achieve cost leadership in acid battery production according to the principles of reducing costs, increasing product quality, preserving the environment, and achieving a sustainable competitive advantage by using the information content of value engineering technology. This will help solve the research problem of the high costs of liquid acid batteries produced by the General Company for Automotive and Equipment Manufacturing - Battery Factory - Babylon 2 Factory, in addition to the increase in environmental pollutants that affect the health of workers as a result of failing to keep pace with rapid developments and not utilizing cost management techniques and modern manufacturing methods. This has led to the inability to compete in the market. Value engineering technology utilizes several methods, such as replacing non-environmentally friendly materials with environmentally friendly alternatives at a lower cost and recycling used batteries, in addition to working on increasing product quality. In order to achieve the research goal, the research population was chosen, represented by the General Company for Automotive and Equipment Manufacturing (Battery Factory), and Babylon 2 Factory was chosen as a sample for the research to apply the research variables to.
Keywords: Cost Leadership, Value Engineering Technique, Competitive Advantage, Recycling